The relationship between tooth loss and pre-elderly nutritional status and quality of life - Widiya Ulfa; Rosa Amalia; Al Supartinah Santoso (Dental Journal, 2023)
Background: Tooth loss leads to decreased masticatory function, which affects nutritional intake. Tooth loss accompanied by poor nutritional status affects quality of life both physically and psychosocially. Purpose: This study was conducted to identify the relationship between number of teeth lost due to nutritional status and quality of life. Methods: A study conducted at Gulai Bancah Primary Health Care in Bukittinggi. Participants were recruited using a non-probability purposive sampling technique. 178 pre-elderlies aged between 45 and 59 years took part in this study. Tooth loss was reported in the dental examination format while nutritional status and quality of life pertaining to dental and oral health were determined using the Mini Nutritional Assessment (MNA) and the Geriatric Oral Health Assessment Index (GOHAI). Pearson correlation and path analysis were utilized to analyze the data. Results: The Pearson correlation test indicated a moderate correlation between tooth loss and nutritional status (r = -0.549) and a strong correlation between the number tooth lost and quality of life (r = -0.742). Pathway analysis confirmed that the direct effect value (beta coefficient = 0.552) was greater than the indirect effect value (beta coefficient = 0.189). The findings indicated that, indirectly, the amount of tooth loss mediated with nutritional status had no significant relationship to quality of life. Conclusion: An increase in tooth loss leads to pre-elderly poor nutritional status and quality of life. However, nutritional status is not an intermediate factor between the number of teeth lost and pre-elderly quality of life.